1992
DOI: 10.1093/bja/69.6.643
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Function and Indocyanine Green Clearance During and After Prolonged Anaesthesia With Propofol

Abstract: We have studied the effects of propofol on hepatic function and clearance of indocyanine green (ICG) in 13 consecutive patients undergoing prolonged plastic and reconstructive surgery. Hepatic function was assessed using serum concentrations of liver-specific glutathione-S-transferase (GST). There were no significant changes in GST activity or plasma clearance of ICG throughout the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Both prolonged halothane and isoflurane anesthesia reduce the clearance of ICG in linear fashion [13,21], presumably resulting from the effects of the anesthetic agents on systemic and splanchnic vessels [6]. In our study, propofol, which has no significant effect on the extraction rate of ICG during prolonged anesthesia [30], was used. However, administration of drugs at the onset of anesthesia or hyperventilation might also affect splanchnic blood flow.…”
Section: Discussionmentioning
confidence: 89%
“…Both prolonged halothane and isoflurane anesthesia reduce the clearance of ICG in linear fashion [13,21], presumably resulting from the effects of the anesthetic agents on systemic and splanchnic vessels [6]. In our study, propofol, which has no significant effect on the extraction rate of ICG during prolonged anesthesia [30], was used. However, administration of drugs at the onset of anesthesia or hyperventilation might also affect splanchnic blood flow.…”
Section: Discussionmentioning
confidence: 89%
“…The effect of prolonged propofol infusion (approximately 10 hours) on the liver condition was analyzed. No significant changes of the GST level in the serum were observed [21]. Similarly, prolonged isoflurane anesthesia did not cause any differences in the levels of GST B1 and B2 in the liver [22].…”
Section: Gst Measurements In Anesthesiamentioning
confidence: 71%
“…19 One study found worsening of liver function attributed to propofol given to a patient with AS during gynecological surgery; 20 whereas another study did not find any deterioration. 21 Because many anesthetic agents undergo hepatic metabolism, the use of muscle relaxants that do not rely on the liver, such as cisatracurium and atracurium, is preferable. For major liver surgery, which is common in patients with AS, hemodynamic changes and reduced cardiac output may cause mesenteric vasoconstriction with decreased regional blood flow.…”
Section: Discussionmentioning
confidence: 99%